Representatividade e ação coletiva: uma avaliação empírica de sua eficácia - Tamaki, Walter Junji (2005)
Representation is a concept of public character that, with the legitimacy concept, is related to the democratic process, to the choice of actors and institutions, normally for elections or suffrages, to be able to act. There is also a 'private representation', obeying, in certain measure, to the democratic logic, by which institutions are formed, receive the grant from being able to act in collective name, and acquire “institutional capacity'. Measures the quality of these institutions and its real influence on the social life is not easy. This dissertation, using theoretical and conceptual basis on representation, collective action and institutional action, search to understand the formation and the consolidation of the ABRAMGE - Brazilian Association of Medicine of Group – evaluating its performance from the perspective of the associates and former-associates and of the current representatives. The basic hypothesis of the work is that the rise in the number of associates reduces the effectiveness of the collective action, harming the representation. The work considers understanding relation between representatives and represented and to measure the general perception that both the sides possess on the character of the representation and its extension and capacity of action, also evaluating if their expectations come being satisfied.